Long-term aerosol size distributions and the potential role of volatile organic compounds (VOCs) in new particle formation events in Shanghai. (1st April 2019) - Ling, Yan; Wang, Yanyu; Duan, Junyan; Xie, Xin; Liu, Yuehui; Peng, Yarong; Qiao, Liping; Cheng, Tiantao; Lou, Shengrong; Wang, Hongli; Li, Xiang; Xing, Xuhuang
Abstract: New particle formation (NPF) events are important phenomena that generate nanoparticles and even fine particles via gas-to-particle conversion. These events have clear effects on aerosol loading, atmospheric chemistry and global climate. Long-term field measurements were used to characterize aerosol size distributions and to examine the role of atmospheric volatile organic compounds (VOCs) in NPF events in the urban environment of Shanghai. Aitken and accumulation particles are dominant and account for 85–95% of the total particles, whereas coarse particles are negligible. Particles in the four size-models show the same seasonality: highest in winter and lowest in autumn. The mean particle size distributions display different patterns of diurnal fluctuation, including bimodal in spring and winter, tri-modal in autumn, and "banana" shaped in summer due to highly frequent NPF events. The geometric mean diameter (GMD) is often 20–30 nm or 40–60 nm. Overall, NPF events occur on 89 days out of 335 measurement days (26.5%), and the newly formed particles have a mean growth rate of 6.28 nm h −1 . Two typical anthropogenic aromatics, benzene and toluene, from traffic emissions closely match the occurrence of NPF events and have a weakly positive correlation with the nucleation particle number concentrations. The enhanced VOCs as precursors of organic vapors may contribute to the growth process of NPF events to some extent (e.g., growth rate) so that newly formed particles can grow into a detectable size. Highlights: Aitken and accumulation particles account for 85–95% of total particles. Aerosol size distributions display different diurnal patterns. The NPFs occur on 89 days out of 335 days with the highest frequency in summer. Two anthropogenic aromatics have correlations with nucleation particle. Enhanced VOCs may contribute to the growth of newly formed particles.